The diversity of entomopathogenic fungi collected from leaves and rhizospheres of rice implementing integrated pest management - Aminudin Afandhi; Elyka Putri Pertiwi; Dicky Prejeki Purba; Tita Widjayanti; Amin Setyo Leksono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Afandhi A, Pertiwi EP, Purba DP, Widjayanti T, Leksono AS. 2020. The diversity of entomopathogenic fungi collected from leaves and rhizospheres of rice implementing integrated pest management. Biodiversitas 21: 2690-2695. Rice is an important food source for most of the world’s population. However, its production often faces pest and disease problems. This study aimed to determine the diversity of entomopathogenic fungi from the leaves and rhizospheres of rice plants, implementing applied integrated pest management (IPM), and to test the pathogenicity of insect fungi species against Spodoptera litura and Tenebrio molitor larvae collection. Entomopathogenic fungi were collected from the leaves and rhizospheres of two rice fields: a field in which IPM is implemented and a conventional field. A total of 24 species were collected from the leaves and rhizospheres in three locations. Pathogenicity test against S. litura larvae was conducted using the Beauveria sp. isolate, whereas pathogenicity test against T. molitor was conducted using the other isolates. Paddy fields in which IPM has been implemented have higher diversity and species richness compared with a conventional field. Location 1 (3 years of IPM implementation) has the highest diversity (2.04 of leaf collection and 1.65 of rhizosphere collection), location 2 has the lowest fungi diversity collected from rhizosphere, whereas location 3 (conventional implementation) has the lowest diversity of leaf collection (1.68). Laboratory testing of Beauveria spp. against S. litura revealed that all species were effective for pest control. Entomopathogenic fungi collected from leaves (Paecilomyces sp.) increased T. molitor mortality by 60%, whereas those isolated from rhizospheres had no effective control of the pest.